Helical Phase-Based Spectroscopy in Matter - Jain, Ashish (Université d'Ottawa / University of Ottawa, 2024)
In the domain of light-matter interaction, a considerable amount of research has been conducted on studying the electric dipole-dominant nonlinear interactions with the fundamental transverse electromagnetic mode of the laser. Moreover, such electric dipole-dominant transitions are often studied using light polarization, associated with spin angular momentum, as an optical probe. In such transition dynamics, the optical phase associated with the wavefront of light is often neglected, as it has been shown to play a minimal role. In the past two decades, it has been demonstrated that light beams can also possess orbital angular momentum associated with structured phase-fronts, possessing a unique helical twist in space. The realization of such helically phased beams, known as helical beams, has inherently led to the investigation of using the helical phase as a probe to study light-matter interaction instead of polarization. Early studies on exploring the helical phase as a tool to examine matter were not conclusive, as the focus was primarily on dipole-dominant transitions. Recently, theoretical studies based on higher-order multipole moments proposed the existence of helical phase-based differential optical response in matter but only limited to certain symmetries. The experimental evidence of such phase-based differential effects in bulk matter has been elusive, without the use of an intermediary. Our research demonstrates the existence of helical phase-dependent dichroism, differential absorption of left- and right-handed helical beams, in different material phases without any intermediary. Such helical dichroism is intrinsic to all material phases and exists irrespective of their symmetry. We also explore the use of phase in the controlled manipulation of matter. The origin of such phase-dependent effects is explained in terms of proposed nonlinear interaction models. The primary objective of this dissertation is to demonstrate the observation of: (i) Helical phase-based dichroism in liquids. We investigate the nonlinear absorption of helical light in chiral and achiral molecules in the liquid phase. Chiral interactions are prevalent in nature, as chirality is a fundamental property of many biological molecules. Two non-superimposable mirror images of a chiral molecule, known as enantiomers, have identical physical and chemical properties when analyzed in achiral environments. Such enantiomers can only be discerned in chiral environments or when the probe is chiral in nature. Typically, the chiral structure of the electric field associated with circularly polarized light is utilized as a chiral probe to induce enantioselective transitions. In this work, we demonstrate the use of the helical phase as an alternative chiral probe with efficient chiral sensitivity. By not involving the chirality associated with light polarization, it is shown that enantioselectivity is a phase effect, and the associated chiral signal can be further controlled. In addition, we show the presence of unique phase-based dichroism in achiral molecules with asymmetrical helical beams. The origin of these effects is modeled by considering multipole transition moments in light-matter interactions. (ii) Helical phase as a chiral probe to differentiate bio-synthesis relevant amino acids. We extend the use of the helical phase as a chiral probe to differentiate amino acid powders in a dissolved state, with varying concentrations. Moreover, we show the phase-based dichroism signal to be an order of magnitude higher relative to conventional linear techniques that use polarization as the chiral probe. The chiral response of powdered enantiomers is explained by considering the symmetry structure of the enantiomeric ground states. (iii) Intrinsic dichroism in amorphous and crystalline solids with helical light. We investigate the nonlinear interaction of helical light in amorphous and crystalline solids. Amorphous solids do not possess long-range order due to the disordered arrangement of atoms and are isotropic in nature. The lack of symmetry in an amorphous solid results in the absence of a circular dichroism signal, which is defined as differential absorption of left- and right-circular polarization. In this work, we demonstrate the existence of intrinsic phase-based dichroism in amorphous solids using helical light beams. We show that helical dichroism is responsive to short- to medium-range order present in amorphous solids and is a phase effect. In addition, we demonstrate that helical dichroism is sensitive to the chirality of crystalline solids, and its strength can be tuned using the superposition of helical and Gaussian beams. The origin of intrinsic dichroism is modeled by considering inter-band electron transitions via multiphoton-assisted tunneling. (iv) Existence of helical dichroism in achiral plasmonic metasurfaces. We demonstrate the presence of helical dichroism in achiral and chiral plasmonic metasurfaces. Our results confirm the existence of dichroism in symmetric material geometries. These results were achieved by probing the helicity-dependent linear absorption of linearly polarized asymmetric helical light beams by the plasmonic metasurfaces. (v) Spatially controlled nano-structuring. We examine the effect of the helical phase on surface morphology modifications. Due to the resolution limitation imposed by the light diffraction limit, nanostructuring has been mostly achieved using lithographic techniques based on electron/ion beams. Here, we introduce a novel helical phase-based ablation method demonstrating spatially controlled manipulation of a silicon surface with a sub-wavelength positional precision of 50 nm. This level of control and accuracy paves the way for new possibilities in nano-printing of materials through methods like laser-induced forward transfer. This dissertation highlights the potentiality of utilizing the helical phase as an alternative chiral probe for examining matter, regardless of its symmetry. The theoretically limitless nature of OAM compared to SAM offers numerous benefits and opens up new possibilities in chiroptical spectroscopy techniques, with potential applications extending up to the pharmaceutical industry. The presence of helical dichroism in amorphous solids provides an alternate approach to determining the short-range order. The design and control of light-matter interactions with helical light introduce new opportunities in the laser processing of materials, ultrafast probing of chiral systems, and nonlinear spectroscopy. The proposed spectroscopy method incorporates the optical phase-based effects, which generally vanish in the electric dipole approximation, by including the electric quadrupole transitions.
Keywords: Spectroscopy; Light-matter interaction; OAM beams; Controlled light absorption; Helical phase-based effects; plasmonics; lithography; optical sensing; optical metrology